Adipose-derived stem cells with miR-150-5p inhibition laden in hydroxyapatite/tricalcium phosphate ceramic powders promote osteogenesis via regulating Notch3 and activating FAK/ERK and RhoA. (1st January 2023) - Wang, Fanglin; Wang, Qiao; Zhao, Yu; Tian, Zhiyu; Chang, Shijie; Tong, Hao; Liu, Ningwei; Bai, Shuling; Li, Xiang; Fan, Jun
Abstract: Adipose-derived mesenchymal stem cells (ADSCs) are multipotent stromal cells and play huge role in forming and repairing bone tissues. Emerging evidence shows that MicroRNAs (miRNAs) are involved in ADSCs differentiation. Here, we explored the role of miR-150-5p and its related mechanisms in ADSCs osteogenesis. Real-time PCR was used to determine miR-150-5p expression during ADSCs osteogenesis. miR-150-5p inhibitors, miR-150-5p ADV or short hairpin RNA (shRNA) of Notch3 were transfected to ADSCs for analyzing the effects on osteogenesis. The mixture of hydroxyapatite/tricalcium phosphate (HA/TCP) ceramic powders and transfected ADSCs was implanted into BALB/C nude mice. Micro-CT and histological methods were performed to evaluate the new bone formation. Compared with negative control (NC) and miR-150-5p overexpression, inhibition of miR-150-5p increased ADSCs osteogenesis by regulating Notch3. MiR-150-5p overexpression decreased the expression of pFAK, pERK1/2, and RhoA, while these were up-regulated when miR-150-5p was inhibited, or notch3 was silenced. Furthermore, miR-150-5p inhibition partially reversed the suppression effect of notch3 knockdown on osteogenesis in vitro and in vivo . This study demonstrated the critical function of miR-150-5p during osteogenesis. The combination of ADSCs with miR-150-5p inhibition and HA/TCP might be a promising strategy for bone damage repair. Statement of significance: Osteoporosis is a common chronic metabolic bone disease in humans. Bone tissue engineering based on mesenchymal stem cells, biomaterials, and growth factors, provides a promising way to treat osteoporosis and bone defects. ADSCs commonly differentiate into adipose cells, they can also differentiate into osteogenic cell lineages. Nucleic acids and protein have usually been considered as regulators of ADSCs osteogenic differentiation. In the current study, we demonstrated the combination of ADSCs with miR-150-5p inhibition and hydroxyapatite/tricalcium phosphate ceramic powders enhanced bone regeneration. Furthermore, miR-150-5p /Notch3 axis regulating osteogenesis via the FAK/ERK1/2 and RhoA pathway was assessed. The current study showed the application of ADSCs in bone regeneration might be a promising strategy for osteoporosis and bone damage repairing. Graphical abstract: Image, graphical abstract